Comunicación corporativa: la gestión del diálogo para recuperar la confianza y derribar barreras culturales en los museos - Dr. David. CORDÓN-BENITO,Dra. Lidia MAESTRO-ESPÍNOLA,Dra. Natalia ABUÍN-VENCES (Fonseca, Journal of Communication, 2023)
After years of upheaval in which institutions have had to face the lack of trust, communication is presented as a fundamental dialogical tool for their recovery. This research focuses on the use of communication by the museum as a cultural institution and a meeting place for communities. The main aim of this work is to delve into the relational perspective of corporate communication and, specifically, into its power to regenerate trust and create community.